IMPACT OF EARLY EPHEMERAL AND TERMINAL DROUGHT ON THE GRAIN YIELD OF THE NAKED OAT (AVENA NUDA L.) - H. Batool; A. Tahir; X. Fang1; T. Yasmin2 (Journal of Animal and Plant Sciences, 2020)
Drought has become more frequent in the recent era due to climate change, which is responsible for reducing the global cereal production. In the present study, two naked oat cultivars; Dingyou7 (Dy7) and Yanmai (Ym) with contrasting drought tolerance were compared for their yield and growth adaptation under different watering schemes at two different stages of plant growth. The plants were grown in a completely randomized design (CRD) under a) well-watered (WW), b) water stressed (WS) conditions; an early ephemeral, c) terminal drought, d) and different field water capacities (FC) of 80%-90%, 60%, 40%, and 20% respectively. The root length (RL), leaf area (LA), leaf number (LN), flower number (FN) and grain yield in two growing seasons in spring to summer and mid-summer to autumn 2018- were measured for all the water treatments at Yuzhong County experiment station, Lanzhou University Gansu, China. The terminal drought and reduced FC were more detrimental to the grain yield as compared with the early ephemeral drought and higher FC as the terminal drought caused 42% and 48% whereas the early ephemeral drought caused 28% and 44% reduction in grain yield of the Dy7 and Ym respectively. All the growth parameters except RL had significant impact (p > 0.05) on the grain yield. This study shows the efficiency of the cultivar Dy7 under drought stress. The fewer number of leaves in the latest cultivar appeared as an important crop adaptation under drought stress to optimize yield. This feature holds potential for improvement of cereal crops yield under drought stress through genetic crop breeding.
Keywords: Naked Oat; Field Water Capacity; Water Stress; Grain Yield; Drought